Reserve Requirementson Bank Deposits a+L558s Implicit Taxes : A Case Study of Italy - Molho, Lazaros (IMF Working Papers; Working Paper ;, 1992)
This paper analyzes the quasi-fiscal effects of Italy's relatively high bank reserve requirements, against the background of growing pressure to align them with those of other EC countries. The paper develops an integrated accounting framework for the measurement of implicit and explicit taxes on the banking system and applies that framework to the Italian experience during the 1980s. Pointing to a lack of transparency in the yield and incidence of the reserve requirement tax, the results reinforce the case for lowering the attendant burden on the Italian banking system. It is estimated that that burden could be halved at a cost to the budget of no more than 0.2 percent of GDP.